Forum: Lévi-Strauss's "The Mathematics of Man". - Martin, John Levi; Seaver, Nick; Maurer, Bill; Moutu, Andrew; Rio, Knut; Corona, Alonso Rodrigo Zamora; Agbetu, Toyin; Green, Sarah (Social Analysis, 2024)
In a recent issue (Vol. 67, No. 2), we published a new translation, by Matthew Carey, of Claude Lévi-Strauss's seminal but often overlooked essay "The Mathematics of Man," which was originally published in French in 1956. As Susanne Küchler suggested in her introduction to the text, Lévi-Strauss's insistence on seeing mathematics as more than just a means of quantification and statistical analysis should be of enduring inspiration to anthropologists interested in how models and other forms of patterned transformation operate within social and cultural life, as well as in how we attempt as anthropologists to gain an analytical handle on them. In continued collaboration with Küchler, in the present issue we have invited anthropologists whose work speaks to these concerns to comment on the contemporary relevance of Lévi-Strauss's argument, encouraging them to be as explicit about the shortcomings and potential dangers of Lévi-Strauss's call to mathematics as they may be of its enduring insights and promise.